Operative Treatment of Spontaneous Pneumothorax and Persistent Air Leaks – The Thoracoscopic Approach - Thapa, B (Nepal Journal of Medical Sciences, 2014)
Background: Spontaneous pneumothoraces are common thoracic surgical problems and when complicated by recurrences and persistent air leaks are often difficult to treat. While conservative non-operative methods were favored in the past, thoracoscopy has made operative treatment more successful, easier and less painful. We reviewed our experience withthoracoscopic management of spontaneous pneumothorax. Methods: We analyzed the retrospective data from the patients who received Video-Assisted Thoracoscopic Surgery for spontaneous pneumothoraces from January 2012 to January 2013 at Manmohan Cardio-thoracic Vascular and Transplant Center. Results: The male to female ratio was 6:1 with mean age 33 years (minimum17 years to maximum70 years). The ratio of primary spontaneous to secondary spontaneous was 5:2. Seventeen of 21 patients had air leaks at operation. Seven of 15 patients with primary spontaneous and 4/6 with secondary spontaneous had prior two or more episodes of pneumothorax. Blebs/ bullae were found in 18/21 patients. In 9/18 patients, the bullae/blebs were stapled while in seven, they were plicated. Only pleurodesis was done in the remaining patients. Additional procedures in the form of decortications were required in three. The chest tube was removed by the second post operative day in 13/21 patients. Prolonged chest tube was required in three patients (persistent leak in two and collection in one patient). One patient needed a subsequent thoracotomy and decortication. Conclusion: Thoracoscopic approach to spontaneous pneumothoraces and persistent air leaks is feasible and safe. Plication of bullae/ blebs can be a viable alternative when stapling devices are not available. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 14-18 DOI: http://dx.doi.org/10.3126/njms.v3i1.10343